Customization of GPRS, and Wi-Fi device drivers for PXA270 of Linux OS based barcode scanner - Prabhakar Pujeri; Sanket S. Naik Dessai (Institute of Advanced Engineering and Science, 2022)
To access any device, it is necessary to have an access point. A device driver is an entry point to access a device. This project is aimed to customize the Wi-Fi and general packet radio service (GPRS) device drivers in Linux OS for PXA270 (Intel Xscale ARM processor). Customizing a device driver is a special way of designing software that can be more easily ported from one architecture to another without rewriting it from scratch. The paper is discussing about the customisation of Wi-Fi and GPRS device driver in Linux OS for PXA270 (Intel Xscale ARM processor). To develop a device driver, it is necessary to understand the processor architecture and Linux kernel internals and other design constraints. Since dynamically loaded driver module is attached to the existing kernel, and any error in the driver will crash the entire system. Resource allocation and implementation for a device is one of the main concerns for device driver developers. The device resources are input/output, memory, IRQs and ports. The required toolchain to build the cross-complier for the Intel Xscale ARM processor was built on Linux platform. The customised device drivers of Wi-Fi, and GPRS was customised, and the customised images are made to port for PXA270 processor architecture on EMX-270 board. With all the supporting parameters the kernel images with drivers are build and ported efficiently. Also, a successful verification and testing had been performed for their functionalities.